2005
DOI: 10.1161/circulationaha.104.528802
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin

Abstract: Background-Bilirubin, a natural product of heme catabolism by heme oxygenases, was considered a toxic waste product until 1987, when its antioxidant potential was recognized. On the basis of observations that oxidative stress is a potent trigger in vascular proliferative responses, that heme oxygenase-1 is antiatherogenic, and that several studies now show that individuals with high-normal or supranormal levels of plasma bilirubin have a lesser incidence of atherosclerosisrelated diseases, we hypothesized that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
118
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(129 citation statements)
references
References 38 publications
8
118
1
2
Order By: Relevance
“…It has been previously reported that bilirubin administration was vasoprotective in a rat model of vascular balloon injury [50], similar to that seen with HO-1 overexpression, suggesting that one component of the cytoprotective effects of HO-1 is likely mediated by bilirubin and/or biliverdin. For example, prior studies have shown that administration of bilirubin inhibited JNK phosphorylation, c-Jun phosphorylation, and endothelial cell apoptosis [51].…”
Section: Discussionsupporting
confidence: 68%
“…It has been previously reported that bilirubin administration was vasoprotective in a rat model of vascular balloon injury [50], similar to that seen with HO-1 overexpression, suggesting that one component of the cytoprotective effects of HO-1 is likely mediated by bilirubin and/or biliverdin. For example, prior studies have shown that administration of bilirubin inhibited JNK phosphorylation, c-Jun phosphorylation, and endothelial cell apoptosis [51].…”
Section: Discussionsupporting
confidence: 68%
“…29 Neointimal proliferation seen two weeks after angioplasty (balloon injury) in wild type rats was virtually absent in the hyperbilirubinemic rats. 30 In concert with those findings, a one-hour local pretreatment of the carotid artery of a naïve, wild type rat with biliverdin was able very significantly to reduce neointima formation following balloon injury (Fig. 1A).…”
Section: Resultssupporting
confidence: 58%
“…When these cells were treated with bilirubin or its precursor biliverdin, 3 H-thymidine uptake was significantly reduced upon FCS stimulation in a dose dependent manner. 30 No significant increase in apoptotic cells was observed after bilirubin/biliverdin treatment at concentrations up to 200mM, but a highly significant portion of the cells were held in the G 0 /G 1 phase when compared to the control (Fig. 1B).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…[9][10][11][12][13][14][15][16][17] Oxidative stress has been linked to the etiology of a wide spectrum of pathophysiological conditions, including cancer, neurological disorders and inflammatory diseases. [18][19][20][21][22] The contribution of hBVR to antioxidant protection offered by induction of the stress-inducible ho-1 was demonstrated by the observation that inhibition of hBVR, by siRNA treatment potentiates ROS-mediated damage to cells and promotes apoptosis. 23 BVR is known as a biliverdin-converting enzyme; however, recent findings have uncovered additional functions of the human reductase that relate to its kinase activity and reflect its structural features.…”
mentioning
confidence: 99%